ACCOUNTING IN ISLAMIC VIEWS - Ayu Sartika Pane (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2020)
ABSTRACTThis paper discusses accounting in the Islamic view starting from introduction, accounting terminology, accounting history, accounting in Islam, and some Islamic accounting theory thinking. As for the existence of accounting in Islam, we can see from a variety of historical evidence as well as from the guidance of the Holy Qur'an which is the main grip and source of law from Muslims. As confirmed in Surah Al-Baqarah verse 282, Islam through the Koran has ordered that the accounting concept that must be followed by transactors and financial statement makers is the concept of social responsibility, justice, and truth. Therefore, it is obligatory for followers of Islam to obey and practice His instructions and commands. In the Qur'an and Hadith, the meaning of accounting terminology is broader covering all human activities in life interacting and dealing in relation to worship and, muamalah in various aspects of life whose ultimate goal is a world and hereafter success (Falah).